THE URGENCY OF STRENGTHENING ELECTRONIC TRANSACTION REGULATIONS IN SUPPORTING THE DIGITAL ECONOMY ECOSYSTEM: A LITERATURE STUDY - Nuni Wulansari; Fajar Nur Wibowo; Asharryadi Noegroho (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The rapid development of the digital economy in Indonesia has driven a major transformation in people's transaction patterns, with electronic transactions becoming an integral part of economic activity. However, this progress is also accompanied by legal challenges, such as consumer protection, data security, and suboptimal law enforcement. This study aims to analyse the urgency of strengthening electronic transaction regulations in supporting the national digital economy ecosystem. The research method used is juridical-normative with a qualitative approach through a literature study of laws and regulations, scientific journals, and official documents. The study results show that although regulations such as the ITE Law, PSTE Regulation, and Personal Data Protection Law have provided a strong legal basis, their implementation still faces various obstacles, such as multiple interpretations of articles, low digital literacy, and weak supervision. Strengthening regulations is needed to create legal certainty, improve consumer protection, and encourage innovation and healthy business competition. Collaboration between the government, business actors, and the community is key in building a safe, inclusive, and highly competitive digital economy ecosystem.